The evolution of Chinese entrepreneurial firms: Township-village enterprises revisited - Xu, Chenggang; Zhang, Xiaobo (International Food Policy Research Institute, 2009)
Township-village enterprises (TVEs) were a major engine of China’s rapid rural industrialization in the past three decades. TVEs also played a key role in fostering entrepreneurship and served as a major stepping-stone for institutional changes when legal protections of private property rights were not in place and the state-owned enterprises (SOEs) were slow to react to changing market demand. As private ownership was gradually recognized legally, TVEs lost their edge in competing with private firms. In the past two decades, industrial clusters with a concentration of private entrepreneurial firms coordinated by local governments have emerged rapidly in many areas. The structures of such firms as TVEs and the subsequent clustering modes of production are an outcome of interaction with other local and macro environments. As the environment changes, a firm’s organization and organizational structure may change as well.